Peningkatan Keterampilan Menulis Karangan Deskripsi Melalui Metode Discovery dengan Menggunakan Media Gambar pada Mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia STKIP Pontianak - Jayanti, Fitri; Fachrurazi, Fachrurazi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to improve students' writing skills on descriftive essay by using the Discovery method aided by the media image. This research was a type of classroom action research. The subjects of this study were students of the Indonesian Language and Literature Study Program STKIP Pontianak amounting to 35 people. The data collected were divided into two categories, namely quantitative and qualitative data. Techniques for collecting qualitative data, namely increasing learning activity activity data, used observation sheets and recording sheets, while for quantitative data collection used test instruments and student performance test. The data collected were described and analyzed using qualitative analysis techniques. The conclusions of the study illustrate the method of finding through image media has made students' writing skills in descriptive essay improved. Students give a good and enthusiastic response when using the discovery method through image media. Based on data and tests that have been done writing skills of students in writing descriptions before doing the action of 60.27%. Then after being given action in the first cycle, student skills reached 72% and in the second cycle student skills increased to 79%.